PELATIHAN PEMBUATAN JARINGAN LAN & WLAN PADA KELURAHAN KALAWALU - Manuhutu, Melda Agnes (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2019)
Technology mastery in the specification of Information and Communication Technology (ICT) isone of the trends in this era, so that it can keep up with the rapid development of the era. It isknown, the development of information technology is currently so rapid. There are manysimulation programs about designing various fields on the internet, both those that are paid andthose that can be downloaded for free by anyone. Technological developments are increasinglyneeded by children, teenagers, young people and parents. It is estimated that it can launch businessunits such as internet cafes or wi-fi homes so as to reduce the number of unemployed youth inKalawalu. The purpose of this community service activity is that the general public in theKalawalu sub-district have capabilities in the field of computer networks and with that capability,young people can support the internet cafe business or home wi-fi so that they can maximizeaccess to the results and reduce the numbers of unemployed in the Kalawalu village.